2013
DOI: 10.1177/0300060513476601
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-γ agonist rosiglitazone reduces secondary damage in experimental spinal cord injury

Abstract: Objective: To investigate the neuroprotective effects of rosiglitazone in a rat traumatic spinal cord injury (SCI) model. Methods: Adult Sprague-Dawley rats (n ¼ 12/group) underwent laminectomy (sham), SCI, SCI and rosiglitazone treatment (2 mg/kg twice daily for 7 days), or SCI and saline injection (vehicle). SCI was induced via dural application of an aneurysm clip. Spinal cord apoptosis and levels of tumour necrosis factor-a (TNFa), interleukin (IL)-1b, myeloperoxidase (MPO) and the apoptosisassociated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Therefore, in line with the in vitro results and along with the higher provisional BBB permeability displayed by MDG548, the present data suggest an increased in vivo potency of MDG548 against MPTP neurotoxicity as compared to rosiglitazone (Nevin et al, 2012). A number of studies have reported the neuroprotective activity of PPARc agonists belonging to the TZDs class in different neurodegenerative conditions (Park et al, 2007;Tureyen et al, 2007;Landreth et al, 2008;Carta, 2013;Li et al, 2013;Lourenco and Ledo, 2013;Ouk et al, 2013;Skerrett et al, 2014). In preclinical PD models, rosiglitazone and pioglitazone displayed neuroprotective properties in rodents and primates (Breidert et al, 2002;Dehmer et al, 2004;Schintu et al, 2009;Swanson et al, 2011;Laloux et al, 2012;Lee et al, 2012;Sadeghian et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, in line with the in vitro results and along with the higher provisional BBB permeability displayed by MDG548, the present data suggest an increased in vivo potency of MDG548 against MPTP neurotoxicity as compared to rosiglitazone (Nevin et al, 2012). A number of studies have reported the neuroprotective activity of PPARc agonists belonging to the TZDs class in different neurodegenerative conditions (Park et al, 2007;Tureyen et al, 2007;Landreth et al, 2008;Carta, 2013;Li et al, 2013;Lourenco and Ledo, 2013;Ouk et al, 2013;Skerrett et al, 2014). In preclinical PD models, rosiglitazone and pioglitazone displayed neuroprotective properties in rodents and primates (Breidert et al, 2002;Dehmer et al, 2004;Schintu et al, 2009;Swanson et al, 2011;Laloux et al, 2012;Lee et al, 2012;Sadeghian et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…The results of another study indicate that enhanced expression levels of PPAR-gamma in microglia following ischemia delays neuronal damage by interfering with glial activation and increases the anti-inflammatory cytokines in response to ischemic damage (Lee et al, 2011). Likewise, the anti-apoptotic action of PPARgamma agonists has been demonstrated (Li et al, 2013). Moreover, according to our results, pioglitazone has the antioxidant property because it decreased the MDA levels (an index of oxidative damage) at injured areas.…”
Section: Discussionsupporting
confidence: 72%
“…A large body of evidence indicates that activation of PPARγ attenuates neural inflammation by reducing inflammatory mediators in ischemic stroke (Culman et al ., 2007), ICH (Zhao et al ., 2007; Aronowski and Zhao, 2011), TBI (Qi et al ., 2010), and SCI (Zhang et al ., 2010; Li et al ., 2013). PPARγ stimulation inhibits the expression of a wide array of pro-inflammatory mediators in microglia and macrophages, including TNF-α, IL-1β, IL-6, iNOS, inducible cyclooxygenase (COX) 2, and the IL-12 family (Bernardo et al ., 2000; Luna-Medina et al ., 2005; Storer et al ., 2005).…”
Section: Pparγ Protects Against Cns Injurymentioning
confidence: 99%